Anti-Fatigue Activity of a Mixture of Stauntonia hexaphylla (Thunb.) Decaisne and Vaccinium bracteatum Thunb. Fruit Extract - Oh, Joohyun; Lee, Yongwook; Han, Yoonyoung; Kim, Jimin; Park, Chansung; Oh, Doolri; Yun, Hyojeong; Lee, Gyuok; Kim, Jaeyong; Choi, Chulyung (Preventive nutrition and food science, 2020)
(Thunb.) Decaisne and Thunb. are commonly used in traditional herbal medicine and food and both exhibit antioxidant and anti-inflammatory effects. Herein, hot-water extracts of (Thunb.) Decaisne and Thunb. fruits (1:1 mixture) were used to produce a complex extract NET-1601. The anti-fatigue activity of NET-1601 was evaluated in an oxidative stress model induced by treating C2C12 myotubes with H O . An exhaustive swimming test (EST) model was established using ICR mice. NET-1601-treated C2C12 myotubes (50, 100, and 200 mg/mL) with H O -induced oxidative stress displayed significantly increased cell viability and ATP content, but significantly decreased levels of reactive oxygen species. All NET-1601-treated EST models demonstrated significantly higher maximum swimming rates than control mice. Furthermore, serum lactate, lactate dehydrogenase activity, non-esterified fatty acid, and intramuscular glycogen levels were higher in NET-1601-treated mice than in control mice. In addition, mRNA levels of regulatory factors involved in muscle mitochondrial fatty acid β-oxidation increased upon NET-1601 treatment. Moreover, catalase, superoxide dismutase, glutathione- -transferase, and liver glutathione content, and antioxidant activity were higher in NET-1601-treated mice than in control mice. Reduced malondialdehyde levels indicated that NET-1601 treatment inhibited exercise-induced lipid peroxidation. Together, these results suggest that NET-1601 retains antioxidant enzyme activity during oxidative stress, simultaneously enhancing both muscle function via glycogen and fatty acid oxidation, thereby exerting a positive effect on recovery from fatigue.